Situation Report: Hungary, 22 July 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Leadership Changes: An Assessment The Leadership Changes: Biographies / by Alfred Reisch HSWP Announces Tough New Stabilization Program / by Karoly Okolicsanyi Prices Increases: Old Problems and Old Solutions / by Judith Pataki New Pension Proposals Highlight Problems of the Elderly / by Edith Markos Secret Politburo Report on Opposition Published The Communist Youth League on Reform Five New Issues of Demokrata The Last Four Vacant Bishoprics Are Filled / by Edith Markos